Gender and age differences in symptoms and health‐related quality of life in patients with atrial fibrillation referred for catheter ablation. Issue 11 (24th September 2019) - Walfridsson, Ulla; Steen Hansen, Peter; Charitakis, Emmanouil; Almroth, Henrik; Jönsson, Anders; Karlsson, Lars O.; Liuba, Ioan; Samo Ayou, Romeo; Poci, Dritan; Holmqvist, Fredrik; Kongstad, Ole; Walfridsson, Håkan
Abstract: Background: Primary indication for catheter ablation of atrial fibrillation (AF) is to reduce symptoms and improve health‐related quality of life (HRQoL). There are data showing differences between the genders and between younger and older patients. To evaluate this, we studied a large Scandinavian cohort of patients referred for catheter ablation of AF. Methods: Consecutive patients filled out the ASTA questionnaire, assessing symptoms, HRQoL, and perception of arrhythmia, prior to ablation. Patients were recruited from four Swedish and one Danish tertiary center. Results: A total of 2493 patients (72% men) filled out the ASTA questionnaire. Women experienced eight of the nine ASTA scale symptoms more often than men. Patients <65 years reported four symptoms more often, only tiredness was more frequent in those ≥65 years ( P  = .007). Women and patients <65 years experienced more often palpitations and regarding close to fainting and this was more common among women, no age differences were seen. Women and men scored differently in 10 of the 13 HRQoL items. Only negative impact on sexual life was more common in men ( P  < .001). Older patients reported more negative influence in four of the HRQoL items and the younger in one; ability to concentrate. Conclusions: Women experienced a more pronounced symptom burden and were more negatively affected in all HRQoL concerns, except for the negative impact on sexual life, where men reported more influence of AF. Differences between age groups were less pronounced. Disease‐specific patient‐reported outcomes measures (PROMs) add important information where gender differences should be considered in the care.